IMPACT OF THE COVID-19 PANDEMIC AND MARTIAL LAW ON THE SATISFACTION OF THE LVIV REGION RESIDENTS WITH THE DIAGNOSTIC RADIOLOGY SERVICE (BASED ON THE RESULTS OF A SOCIOLOGICAL SURVEY) - Galyna Shcherbata; Oksana Kovalska (Acta Medica Leopoliensia)
The aim of the study is to assess the satisfaction of the population of the Lviv region with the work of the diagnostic radiology service, to identify problems and ways to solve them.